Justice versus judiciary : justice enthroned or entangled in India - Ranjan, Sudhanshu 1962- (New Delhi : Oxford University Press, 2019)
Friedrich Nietzsche believed his own work represented the dawning of a new historical era, and, despite the fact that he lived most of his sane life suffering in obscurity, it is not an exaggeration to say that his vision helped lay the foundations for modernism in style, substance and attitude. Nietzsche was himself devoted to the modern, for he reinterpreted every philosophy, every historical figure and event, every movement that came before him. This reconceptualization of the past through new, modern eyes opened up Nietzsche's thinking to exploring daring possibilities for the future. This prophetic boldness, which is so unique to his style, seduced the modernist generation across the spectrum. He was read by early Zionists as well as by Nazi racial theorists; by Thomas Mann and as well as by Salvador Dali. His influence stretched from psychoanalysis to anarchist politics.
Keywords: India. -- Supreme Court; Justice, Administration of -- India; Court congestion and delay